Curing adhesive, S-type epoxy compound with binaphthyl as well as preparation method and application of S-type epoxy compound
By using the combination of S-type epoxy compounds with binaphthyl groups with oligomers and other resins, active monomers or additives, the existing cured glue has been solved with low refractive index and poor compatibility of inorganic nanoparticles, and an optical film with high refractive index, low yellowness, high light transmittance and high temperature resistance is achieved.
Patent Information
- Application Number
- CN202510407904.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-02
- Publication Date
- 2025-05-02
- Estimated Expiration
- 2045-04-02
AI Technical Summary
The refractive index of existing cured glues is difficult to reach 1.6, and the incompatibility of inorganic nanoparticles with organic cured materials affects its performance.
An optical film with high refractive index, low yellowness, high light transmittance and high temperature resistance is designed by combining with oligomers and other resins, active monomers or additives.
The high refractive index, low yellowness, high light transmittance and high temperature resistance of the cured glue are achieved, which broadens its application window and avoids the compatibility of inorganic nanoparticles with organic cured materials.
Smart Images

Figure SMS_9 
Figure SMS_10 
Figure SMS_11
Abstract
Description
Technical Field
[0001] The present application relates to the field of optical materials, and in particular to a curing adhesive, an S-type epoxy compound having a binaphthyl group, and a preparation method and application thereof. Background Art
[0002] In many current application fields, such as optical communication technology, eyeglass lenses, lenses, display panels, and optical waveguides, high refractive index materials are needed to achieve photon integration to increase system efficiency, increase brightness, protect devices, etc. However, the refractive index of most organic curing materials is relatively low, generally in the range of 1.45~1.55, and the refractive index of the prepared curing glue is difficult to reach 1.6.
[0003] At present, the conventional strategy to improve the refractive index of the curing adhesive system is to introduce a certain amount of inorganic nanoparticles into the organic curing material. The more inorganic nanoparticles are used, the higher the refractive index is. However, the incompatibility between inorganic nanoparticles and organic curing materials makes it difficult for the inorganic nanoparticles to be stably dispersed in the organic curing material, which in turn affects the refractive index, yellowness and transmittance of the curing adhesive system, making it difficult to meet market demand.
[0004] Therefore, in order to meet market demand, it is necessary to design a new all-organic curing system or an organic-inorganic curing system with good compatibility so that the curing glue system has a high refractive index, low yellowness, high light transmittance and high temperature resistance. Summary of the invention
[0005] Therefore, the technical problem to be solved by the present application is to overcome the above-mentioned defects in the prior art, and its purpose is to provide a curing adhesive, which includes an S-type epoxy compound with a naphthyl group. The S-type epoxy compound with a naphthyl group has the advantages of high refractive index and low yellowness, which is conducive to the preparation of an optical film with high refractive index, low yellowness, high transmittance and high temperature resistance by using the curing adhesive.
[0006] In a first aspect of the present application, a curing adhesive is provided, comprising an S-type epoxy compound having a binaphthyl group, wherein the S-type epoxy compound having a binaphthyl group comprises a compound having a structure shown in Formula I,
[0007] Formula I,
[0008] Wherein R1 includes substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 1-10 Alkyleneoxy, substituted or unsubstituted C 3-10 At least one of a cycloalkoxy group and a substituted or unsubstituted phenoxy group.
[0009] The present application study found that due to the advantages of the S configuration, the optical film prepared by the curing reaction of the curing adhesive containing the S-type epoxy compound with the naphthyl group not only has the advantage of a high refractive index, but more importantly, has the significant advantages of lower yellowness, higher light transmittance and better temperature resistance.
[0010] In any embodiment, the curing glue further comprises the oligomer of the S-type epoxy compound having a binaphthyl group, and the mass ratio of the oligomer of the S-type epoxy compound having a binaphthyl group to the S-type epoxy compound having a binaphthyl group is not higher than 0.055, preferably not higher than 0.05.
[0011] The introduction of S-type oligomers of epoxy compounds with binaphthyl groups in the curing adhesive can not only avoid the influence of compatibility to the greatest extent, but more importantly, it can effectively improve the refractive index of the curing adhesive, realize the design of a high refractive index system, and broaden its application window.
[0012] In any embodiment, R1 includes substituted or unsubstituted C 1-10 Alkyleneoxy, substituted or unsubstituted C 3-10 At least one of a cycloalkoxy group and a substituted or unsubstituted phenoxy group.
[0013] The second aspect of the present application provides a method for preparing an S-type epoxy compound having a binaphthyl group, comprising:
[0014] Under reactive conditions, reacting raw materials including (S)-(-)-1,1'-binaphthol and epoxy halogenated alkyl to prepare the S-type epoxy compound having a binaphthyl group;
[0015] Wherein, the epoxyhaloalkane comprises at least one of the compound of the structure shown in Formula II and the compound of the structure shown in Formula III,
[0016] Formula II, Formula III,
[0017] In the formula, R 11 , R 12 Each independently includes substituted or unsubstituted C 1-10 At least one of the alkylene groups, Y1 and Y2 each independently include at least one of bromine, fluorine, chlorine and iodine.
[0018] The preparation method has readily available raw materials, simple operation and low production cost. The prepared S-type epoxy compound with binaphthyl groups has the advantages of high refractive index and low yellowness.
[0019] In any embodiment, the raw material further comprises a compound of the structure shown in Formula IV,
[0020] Formula IV,
[0021] In the formula, R 13 Including substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 At least one of cycloalkyl and substituted or unsubstituted phenyl, and X1 includes at least one of bromine, fluorine, chlorine and iodine.
[0022] The introduction of the compound having the structure shown in Formula IV is beneficial to reducing the yellowness of the S-type epoxy compound having a binaphthyl group, or improving its transmittance and refractive index.
[0023] The third aspect of the present application provides an S-type epoxy compound having a binaphthyl group, which is prepared by the preparation method of the second aspect of the present application.
[0024] In a fourth aspect, the present application provides the use of the curing adhesive according to the second aspect of the present application in an optical device. DETAILED DESCRIPTION
[0025] The following specifically discloses the curing glue, S-type epoxy compound with binaphthyl group, preparation method and application implementation methods of the present application. However, there may be cases where unnecessary detailed descriptions are omitted. For example, there are cases where detailed descriptions of well-known matters and repeated descriptions of actually the same structure are omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate the understanding of those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present application and is not intended to limit the subject matter described in the claims. Any product that is identical or similar to the present application that is obtained by anyone under the inspiration of the present application or by combining the features of the present application with other prior arts falls within the scope of protection of the present application.
[0026] The "range" disclosed in the present application is defined in the form of a lower limit and an upper limit, and a given range is defined by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundaries of a particular range. The range defined in this way can include or exclude end values, and can be arbitrarily combined, that is, any lower limit can be combined with any upper limit to form a range. For example, the numerical range "ab" represents an abbreviated representation of any real number combination between a and b, where a and b are both real numbers. For example, the numerical range "0-7" means that all real numbers between "0-7" have been fully listed in this article, and "0-7" is just an abbreviated representation of these numerical combinations. In addition, when a certain parameter is expressed as an integer ≥3, it is equivalent to disclosing that the parameter is, for example, an integer of 3, 4, 5, 6, 7, 8, 9, 10, 11, etc.
[0027] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution.
[0028] Unless otherwise specified, all technical features and optional technical features of this application can be combined with each other to form a new technical solution.
[0029] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, the method includes steps (1) and (2), which means that the method may include steps (1) and (2) performed sequentially, or may include steps (2) and (1) performed sequentially. For example, mentioning that the method may also include step (3) means that step (3) may be added to the method in any order, for example, the method may include steps (1), (2) and (3), or may include steps (1), (3) and (2), or may include steps (3), (1) and (2, etc.
[0030] If there is no special explanation, the "include" and "comprising" mentioned in this application are open-ended or closed-ended. For example, the "include" and "comprising" may mean that other components not listed may also be included or only the listed components may be included or only the listed components may be included.
[0031] If not specifically stated, in this application, the term "or" is inclusive. For example, the phrase "A or B" means "A, B, or both A and B". More specifically, any of the following conditions satisfies the condition "A or B": A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0032] The present application provides a curing adhesive, which includes an S-type epoxy compound having a binaphthyl group, wherein the S-type epoxy compound having a binaphthyl group includes a compound having a structure shown in Formula I,
[0033] Formula I,
[0034] Wherein R1 includes substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 At least one of a cycloalkyl group and a substituted or unsubstituted phenyl group.
[0035] In this article, the term "S-type epoxy compound having a binaphthyl group" refers to an epoxy compound having an S-type configuration of the chiral center and having a binaphthyl group; the specific rotation of the epoxy compound having a binaphthyl group in this application is obtained by testing with a polarimeter, and the specific rotation of the S-type epoxy compound having a binaphthyl group is "-", and the specific rotation of the R-type epoxy compound having a binaphthyl group is "+".
[0036] As used herein, the term "specific optical rotation" refers to the rotation angle of the light vibration plane caused by light having a wavelength of 589 nm passing through a solution of unit length (1 dm) and unit concentration (g / ml) at a temperature of 20°C.
[0037] In this context, the term "substituted or unsubstituted" means that at least one hydrogen of the substituent is replaced by deuterium, halogen, cyano, C 1-10 Alkyl, C 1-10 Cycloalkyl, C 6-20 Aryl, C 2-20 heteroaryl or a combination thereof.
[0038] In this article, the curing method of the curing adhesive includes but is not limited to light curing or heat curing. When the curing adhesive adopts the light curing method, the curing adhesive also includes a photoinitiator; when the curing adhesive adopts the heat curing method, the curing adhesive does not include a photoinitiator.
[0039] Research has found that the introduction of phenyl groups into organic curing materials is beneficial to improving their refractive index. The S-type epoxy compounds with binaphthyl groups in the present application not only have the advantages of high refractive index and low yellowness, but more importantly, compared with R-type epoxy compounds with binaphthyl groups or mixed-type epoxy compounds with binaphthyl groups, the configuration of S-type epoxy compounds with binaphthyl groups is more advantageous in the optical field, which is beneficial to its molecular arrangement during the curing process, and an optical film with lower refractive index and higher light transmittance is obtained, which broadens the application window of the curing adhesive.
[0040] It can be understood that due to the influence of molecular configuration, during the curing process, compared with the curing reaction of R-type epoxy compounds with binaphthyl groups, or the curing reaction of R-type and S-type mixed epoxy compounds with binaphthyl groups, the curing reaction of S-type epoxy compounds with binaphthyl groups is more conducive to the preparation of optical films with lower yellowness and higher transmittance, and the optical film prepared with the curing glue containing S-type epoxy compounds with binaphthyl groups has significantly lower yellowness than the R-type epoxy compound system with binaphthyl groups (R-type epoxy compounds with binaphthyl groups / S-type epoxy compounds with binaphthyl groups mixed system) after high-temperature storage, and has more optical advantages.
[0041] In some embodiments, the specific rotation of the S-type epoxy compound having a binaphthyl group is -50 to -30 (°·ml) / (dm·g). In some embodiments, the specific rotation of the S-type epoxy compound having a binaphthyl group may be selected as -50 (°·ml) / (dm·g), -48 (°·ml) / (dm·g), -46 (°·ml) / (dm·g), -45 (°·ml) / (dm·g), -44 (°·ml) / (dm·g), -42 (°·ml) / (dm·g), -40 (°·ml) / (dm·g), -38 (°·ml) / (dm·g), -36 (°·ml) / (dm·g), -35 (°·ml) / (dm·g), -34 (°·ml) / (dm·g), -32 (°·ml) / (dm·g), -30 (°·ml) / (dm·g), or a value in the range consisting of any two of the above values.
[0042] The optical film prepared by the curing glue containing S-type epoxy compound with binaphthyl group with specific rotation of -50~-30 (°·ml) / (dm·g) in the present application has the significant advantages of high refractive index, low yellowness, high transmittance and high temperature resistance.
[0043] In some embodiments, the epoxy value of the S-type epoxy compound having a binaphthyl group is 0.184 to 0.502 mol / 100 g. In some embodiments, the epoxy value of the S-type epoxy compound having a binaphthyl group can be selected from 0.184 mol / 100 g, 0.185 mol / 100 g, 0.200 mol / 100 g, 0.220 mol / 100 g, 0.240 mol / 100 g, 0.250 mol / 100 g, 0.260 mol / 100 g, 0.280 mol / 100 g, 0.300 mol / 100 g, 0.320 mol / 100 g, 0.340 mol / 100 g. 100g, 0.350mol / 100g, 0.360mol / 100g, 0.380mol / 100g, 0.400mol / 100g, 0.420mol / 100g, 0.440mol / 100g, 0.450mol / 100g, 0.460mol / 100g, 0.480mol / 100g, 0.500mol / 100g, 0.502mol / 100g, or a value in the range consisting of any two of the above values.
[0044] In the present application, the epoxy value of the S-type epoxy compound having a binaphthyl group can be tested by any known method. As an example, the epoxy value of the S-type epoxy compound having a binaphthyl group is measured by hydrochloric acid-acetone titration method, and reference can be made to ASTM-D1652 standard.
[0045] In some embodiments, the refractive index of the S-type epoxy compound having a binaphthyl group is 1.64 to 1.70.
[0046] In the present application, the refractive index of the S-type epoxy compound having a binaphthyl group can be tested by any known method. As an example, the refractive index of the S-type epoxy compound having a binaphthyl group is tested by using an Abbe refractometer (Abbemat 300), the test temperature is 20°C, and the S-type epoxy compound having a binaphthyl group to be tested is directly dropped on the prism of the Abbe refractometer to test its refractive index.
[0047] The refractive index of the S-type epoxy compound having a binaphthyl group in the present application exceeds 1.6. For application requirements with a refractive index of 1.6 to 1.7, a fully organic curing adhesive can be prepared.
[0048] In some embodiments, the curing glue further comprises an S-type oligomer of an epoxy compound having a binaphthyl group, and the mass ratio of the S-type oligomer of an epoxy compound having a binaphthyl group to the S-type epoxy compound having a binaphthyl group is not higher than 0.055. In some embodiments, the mass ratio of the S-type oligomer of an epoxy compound having a binaphthyl group to the S-type epoxy compound having a binaphthyl group can be selected as 0.0001, 0.001, 0.01, 0.02, 0.03, 0.04, 0.05, 0.055, or any value in the range formed by any two of the above points.
[0049] The present application has found that the introduction of S-type oligomers of epoxy compounds with binaphthyl groups in the curing adhesive can not only avoid the influence of compatibility to the greatest extent, but more importantly, can effectively improve the refractive index of the curing adhesive, realize the design of high refractive index system, and broaden its application window. Too high content of S-type oligomers of epoxy compounds with binaphthyl groups will significantly affect the yellowness and light transmittance of the optical film prepared by the curing adhesive.
[0050] In some embodiments, R1 includes substituted or unsubstituted C 3-10 Alkylene, substituted or unsubstituted C 3-10 At least one of alkyleneoxy groups.
[0051] The present application has found that R1 is selected from a long-chain alkylene group or an alkyleneoxy group, which is further beneficial to reducing the yellowness of the optical film prepared by the cured adhesive and improving the light transmittance.
[0052] In some embodiments, R1 includes substituted or unsubstituted C 3-10 At least one of a cycloalkoxy group and a substituted or unsubstituted phenoxy group.
[0053] The present application has found that R1 is selected from cycloalkyl or phenyl, which is further beneficial to the improvement of the refractive index of the optical film prepared by the cured adhesive.
[0054] In some embodiments, the curing adhesive further includes at least one of a resin, an active monomer, an auxiliary agent, and a solvent.
[0055] The S-type oligomers of epoxy compounds with binaphthyl groups have high adaptability. The resin, active monomer or auxiliary agent introduced into the curing adhesive has good compatibility with the S-type oligomers of epoxy compounds with binaphthyl groups. The cured adhesive has high refractive index, low yellowness, high transmittance and high temperature resistance.
[0056] In some embodiments, the resin includes at least one of epoxy acrylate resin, polyurethane acrylate resin, polyether acrylate resin, polyester acrylate resin, polyurethane epoxy resin, polyurethane resin, and silicone resin.
[0057] In some embodiments, the active monomer includes at least one of an epoxy monomer, an acrylate monomer, and a styrene monomer, wherein the epoxy monomer includes ethylene oxide, propylene oxide, butylene oxide, an alkyl ethylene oxide having an alkyl carbon number of 3 to 20, styrene oxide, 1,3-butadiene diepoxide, 1,5-hexadiene diepoxide, 1,7-octadiene diepoxide, 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, styrene oxide, alkyl glycidyl ether, aromatic glycidyl ether, alkenyl glycidyl ether, alkynyl glycidyl ether, and cyclohexene oxide, and the acrylate monomer includes tricyclodecane dimethanol diacrylate, tricyclodecane dimeth ... Decane dimethanol dimethyl diacrylate, neopentyl glycol diacrylate, dipropylene glycol diacrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol diacrylate, ethylene phthalate diacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol diacrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol dimethacrylate, propoxylated neopentyl glycol diacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, dipropylene glycol diacrylate, ethoxylated bisphenol A dimethacrylate, tripropylene glycol diacrylate, pentaerythritol dimethylacrylate Acrylate, trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol hexaacrylate, urethane di(meth)acrylate, bisphenol A propylene glycol dimethacrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, isobornyl methacrylate, isobornyl acrylate, isooctyl acrylate, isooctyl methacrylate, tetrahydrofuran acrylate, tetrahydrofuran methacrylate, 2-phenoxyethyl acrylate, pentaerythritol (meth)acrylate, n-butyl acrylate, isodecyl acrylate, lauric acid acrylate, cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, 4 - at least one of tert-butyl cyclohexyl acrylate, dicyclopentenyl acrylate, octadecyl methacrylate, butyl acrylate, isodecyl acrylate, isodecyl methacrylate, lauryl acrylate, lauryl methacrylate, glycidyl methacrylate, 2-phenoxyethyl methacrylate, isodecyl acrylate, vinyl acetate, dicyclopentenyl ethoxylated methacrylate, and 4-tert-butyl cyclohexyl acrylate, and the styrene monomer includes at least one of styrene, vinyl toluene, α-methyl styrene, p-methyl styrene, α-butyl styrene, 4-n-butyl styrene, divinylbenzene, 2,4-dimethylstyrene, ethyl styrene, and p-tert-butyl styrene.
[0058] In some embodiments, the auxiliary agent includes at least one of a photoinitiator, a thermal curing agent, a leveling agent, an antioxidant, and a dispersant.
[0059] In some embodiments, the photoinitiator includes at least one of a diaryliodonium salt, a triarylsulfonium salt, a hexafluoroantimonate sulfonium salt, and an aromatic diazonium salt; the photoinitiator includes at least one of 2-hydroxy-2-methyl-1-phenyl-1-propanone, 1-hydroxycyclohexyl phenyl ketone, 2,4,6-trimethylbenzoyldiphenylphosphine oxide, isopropylthioxanthone, 2,2-dimethoxy-2-acetophenone, α-amino-1-phenyl-1-propanone, 2-hydroxythioxanthone, α-aminophenylacetophenone hydrochloride, phenacylpyridine oxalate, photoinitiator UV6992, photoinitiator UV6976, photoinitiator 819, photoinitiator 907, photoinitiator ITX, photoinitiator 1173, photoinitiator TPO, photoinitiator 184, photoinitiator 1176, and photoinitiator 6976.
[0060] In some embodiments, the thermal curing agent includes at least one of aliphatic tertiary amines, aromatic tertiary amines, quaternary ammonium salts, sulfonium salts, and guanidine. In some embodiments, the thermal curing agent includes at least one of di(4-aminophenyl)sulfone, di(4-aminophenyl)ether and 2,2-di(4-aminophenyl)propane, dimethylaminopropylamine, N-methyl-4-methylpyridinium hexafluorophosphate, fluorenediamine, tetramethylguanidine, and dicyandiamide.
[0061] In some embodiments, the leveling agent includes at least one of TEGO Glide 410, BYK346, BYK333, BYK3499, BYK3455, BYK301, EFKA3777, and Evonik420.
[0062] In some embodiments, the dispersant includes at least one of BYK163, BYK191, BYK180, BYK110, EFKA4310, EFKA4010, EFKA4560, SURFYNOL 104E, Tego dispers 655, and SN-Dispersant 5027.
[0063] In some embodiments, the antioxidant includes at least one of antioxidant 1076 , antioxidant 1010 , and antioxidant 168 .
[0064] In some embodiments, the solvent includes at least one of propylene glycol methyl ether acetate, propylene glycol methyl ether, methyl ethyl ketone, methyl isobutyl ketone, butyl acetate, ethanol.
[0065] In some embodiments, based on the total mass of the curing glue, the mass content of the S-type epoxy compound having a binaphthyl group is 10% to 90%, the mass content of the solvent is 5% to 88%, the mass content of the auxiliary agent is 0.1% to 5%, the mass content of the resin is 0% to 30%, and the content of the active monomer is 0% to 30%. In some embodiments, based on the total mass of the curing glue, the mass content of the S-type epoxy compound having a binaphthyl group can be selected to be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, or any value in the range formed by any two of the above points, the mass content of the solvent is 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80%, 85%, 88%, or any value in the range formed by any two of the above points, and the mass content of the auxiliary agent is 0.1%, 0.5% or more. , 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5%, or any value in the range formed by any two of the above points; the mass content of the resin is 0%, 0.001%, 0.01%, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, or any value in the range formed by any two of the above points; the content of the active monomer is 0%, 0.001%, 0.01%, 0.1%, 0.5%, 1%, 5%, 10%, 15%, 20%, 25%, 30%, or any value in the range formed by any two of the above points.
[0066] In the present application, the S-type epoxy compound with a naphthyl group can be mixed with other resins, active monomers or additives in any proportion within the range of 10wt% to 90wt% to obtain a cured adhesive. The optical adhesive prepared by the cured adhesive has a high refractive index, low yellowness, high transmittance and high temperature resistance.
[0067] In some embodiments, the curing adhesive further includes nanoparticles, and the nanoparticles include at least one of SiO2, ZnS, ZnO, CeO2, GeO2, Ta2O5, Bi4Ti3O2, Nb2O5, ITO, HfO2, SnO2, MoO3, Sb2O3, Sb2O5, Nd2O3, ZrO2, and TiO2.
[0068] In some embodiments, the mass content of the nanoparticles is 0% to 60% based on the total mass of the curing glue. In some embodiments, the mass content of the nanoparticles is optionally 0%, 5%, 10%, 15%, 20%, 25%, 30%, 35%, 40%, 45%, 50%, 55%, 60%, or any value in the range of any two of the above points based on the total mass of the curing glue.
[0069] The research of this application found that by controlling the mass content of nanoparticles within 60%, S-type epoxy compounds with binaphthyl groups have good compatibility with nanoparticles, which can avoid the impact of compatibility issues on the optical properties (refractive index, yellowness, light transmittance, temperature resistance) of the optical film to the greatest extent. The introduction of SiO2 into the curing glue can improve its wear resistance and mechanical strength, and the introduction of high-refractive nanoparticles such as ZrO2 and TiO2 into the curing glue can improve its refractive index and mechanical strength.
[0070] The present application also provides a method for preparing an S-type epoxy compound having a binaphthyl group, comprising:
[0071] Under reactive conditions, raw materials including (S)-(-)-1,1'-binaphthol and epoxy halogenated alkyl are reacted to prepare an S-type epoxy compound having a binaphthyl group;
[0072] Wherein, the epoxyhaloalkane comprises at least one of the compound of the structure shown in Formula II and the compound of the structure shown in Formula III,
[0073] Formula II, Formula III,
[0074] In the formula, R 11 , R 12 Each independently includes substituted or unsubstituted C 1-10 At least one of the alkylene groups, Y1 and Y2 each independently include at least one of bromine, fluorine, chlorine and iodine.
[0075] The preparation method has readily available raw materials, simple operation and low production cost. The prepared S-type epoxy compound with binaphthyl groups has the advantages of high refractive index and low yellowness.
[0076] In some embodiments, the molar ratio of the epoxy halogenated alkyl to (S)-(-)-1,1'-bi-2-naphthol is (4-50): 1. In some embodiments, the molar ratio of the epoxy halogenated alkyl to (S)-(-)-1,1'-bi-2-naphthol is 4:1, 5:1, 10:1, 15:1, 20:1, 25:1, 30:1, 35:1, 40:1, 45:1, 50:1, or any ratio within the range of any two of the above ratios.
[0077] In some embodiments, the reaction temperature is 40-110°C, and the reaction time is 2-6 hours. In some embodiments, the reaction temperature can be 40°C, 50°C, 6°C, 70°C, 80°C, 90°C, 100°C, 110°C, or any value in the range formed by any two of the above points, and the reaction time can be 2 hours, 2.5 hours, 3 hours, 3.5 hours, 4 hours, 4.5 hours, 5 hours, 5.5 hours, 6 hours, or any value in the range formed by any two of the above points.
[0078] In some embodiments, the catalyst of the reaction comprises a quaternary ammonium salt. In some embodiments, the catalyst of the reaction comprises at least one of tetrabutylammonium bromide, benzyltriethylammonium chloride, and tetramethylammonium bromide.
[0079] In some embodiments, the mass ratio of the catalyst to the (S)-(-)-1,1'-bi-2-naphthol is (0.01-0.1): 1. In some embodiments, the mass ratio of the catalyst to the (S)-(-)-1,1'-bi-2-naphthol can be selected as 0.01: 1, 0.02: 1, 0.03: 1, 0.04: 1, 0.05: 1, 0.06: 1, 0.07: 1, 0.08: 1, 0.09: 1, 0.1: 1, or any ratio in the range of any two of the above ratios.
[0080] Controlling appropriate reaction conditions is beneficial to the preparation of S-type epoxy compounds with binaphthyl groups having high refractive index and low yellowness.
[0081] In some embodiments, the epihaloalkylene includes at least one of epichlorohydrin, 1,2-epichlorobutylene, 2-(4-chlorobutyl)oxirane, (8-chlorooctyl)oxirane, epibromohydrin, epiiodohydrin, 2-(chloromethyl)-2-methyloxirane, 2-(bromomethyl)-2-methyloxirane, and 3-chloro-2-methyl-1,2-epoxypropane.
[0082] In some embodiments, the raw material further comprises a compound of the structure shown in Formula IV,
[0083] Formula IV,
[0084] In the formula, R 13 Including substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 At least one of cycloalkyl and substituted or unsubstituted phenyl, and X1 includes at least one of bromine, fluorine, chlorine and iodine.
[0085] In some embodiments, the compound of the structure shown in Formula IV includes at least one of 2-chloroethanol, 3-bromo-1-propanol, 1-chloro-2-propanol, 4-bromo-1-butanol, 4-bromo-1-cyclohexanol, 2-chlorocyclohexanol, 3-bromocyclopentanol, 4-fluorocycloheptanol, 2-iodocyclohexanol, 2-bromocycloheptanol, m-hydroxyphenethyl bromide, and 2-iodophenol.
[0086] The introduction of the compound having the structure shown in Formula IV is beneficial to reducing the yellowness of the S-type epoxy compound having a binaphthyl group, or improving its transmittance and refractive index.
[0087] The present application also provides an S-type epoxy compound having a binaphthyl group, which is prepared by the preparation method in some embodiments.
[0088] The present application also provides applications of the curing adhesive in some embodiments in optical devices.
[0089] Optical devices include, but are not limited to, eyeglass lenses, lens lenses, optical communication devices or display panels.
[0090] Example
[0091] The following examples are provided for a better understanding of the present invention, are not limited to the best mode of implementation, and do not limit the content and scope of the present invention. If no specific experimental steps or conditions are specified in the examples, the operation or conditions of the conventional experimental steps described in the literature in this area can be carried out. If the manufacturer is not specified for the reagents or instruments used, they are all conventional reagent products that can be obtained commercially. If not otherwise specified, the raw materials in the examples and comparative examples are purchased from Sigma-Aldrich.
[0092] 1. Preparation method
[0093] Example 1
[0094] Preparation of S-type epoxy compounds with binaphthyl groups: In a 100 mL three-necked flask equipped with a condenser, a magnetic stirrer and a nitrogen interface, 5.73 g of (S)-(-)-1,1'-binaphthol, 37 g of epichlorohydrin and 0.287 g of tetrabutylammonium bromide were added, the temperature was raised to 105°C, the reaction was continued for 3.5 h, and then the heating was stopped and the temperature was lowered to 50°C. 6.93 g of 30 wt% NaOH solution was added dropwise using a constant pressure dropping funnel. The addition was completed slowly within 1.5 h. After the reaction was continued for 2 h, the heating was stopped. After the reaction is completed, the white solid is filtered out and washed with deionized water for 3 to 4 times until the solution is neutral. Anhydrous sodium sulfate is added to dry and remove water, filtered, and then epichlorohydrin is distilled off under reduced pressure. The mixture is heated in an oven at 150°C for 16 hours to obtain an S-type epoxy compound with a binaphthyl group with a yield of 92%, an epoxy value of 0.463 mol / 100 g, and a refractive index of 1.65.
[0095] Infrared spectrum: 3021cm -1 、2982cm -1 (benzene ring CH bond); 2897cm -1 (alkyl CH bond); 1600cm -1 、1499cm -1 (Benzene ring C=C bond); 920cm -1 (Epoxy group).
[0096] 1H NMR (400 MHz, CDCl3): δ 6.7-7.9 (12H, benzene ring); δ 3.9-4.2 (4H, -CH2- connected to the epoxy group); δ 3.3 (2H, -CH- in the epoxy group); δ 2.7-2.8 (4H, -CH2- in the epoxy group).
[0097] Preparation of curing adhesive: 5 g of the above-mentioned S-type epoxy compound with binaphthyl group was dissolved in 4.71 g of propylene glycol methyl ether acetate, 0.25 g of photoinitiator UV6992 and 0.04 g of leveling agent BYK381 were added, and the mixture was heated and mixed at 120°C for 20 min, and then dispersed under magnetic stirring at 600 rpm for 0.5 h to obtain curing adhesive.
[0098] Preparation of optical film: Place a 4-inch diameter glass sheet on a Laurell spin coating device, and drip 4 ml of the above curing glue on the glass sheet with a pipette to prepare a coating. The spin coating speed is 2000 rpm, the spin coating time is 1 min, and the coating is cured under 365 nm UV-LED, and the curing energy is 3600 mJ / cm 2 , preparing optical films.
[0099] Example 2
[0100] The preparation methods of the S-type epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Example 2 are similar to those of the S-type epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Example 1, except that 4-bromo-1-butanol is introduced into the preparation process of the S-type epoxy compound having a binaphthyl group of Example 1. The preparation method of the S-type epoxy compound having a binaphthyl group is as follows:
[0101] In a 100 mL three-necked flask equipped with a condenser, a magnetic stirrer and a nitrogen interface, 5.73 g of (S)-(-)-1,1'-bi-2-naphthol and 100 mL of tetrahydrofuran were added, followed by 0.31 g of KOH, 0.013 g of KI and 0.57 g of 4-bromo-1-butanol. The mixture was refluxed at 85 °C for 10 h under a nitrogen atmosphere, then cooled, extracted with ethyl acetate and dried to obtain an intermediate.
[0102] The above intermediate, 37g of epichlorohydrin, and 0.287g of tetrabutylammonium bromide were heated to 105°C and reacted for 3.5h, then the heating was stopped, the temperature was lowered to 50°C, and 6.93g of 30wt% NaOH solution was added dropwise using a constant pressure dropping funnel, and the addition was completed slowly within 1.5h. After reacting for 2h, the heating was stopped. After the reaction was completed, the white solid was filtered out and washed with deionized water for 3 to 4 times until the solution was neutral, anhydrous sodium sulfate was added to dry and remove water, filtered, and then the epichlorohydrin was removed by vacuum distillation. The mixture was heated in an oven at 150°C for 16h to obtain an S-type epoxy compound with a binaphthyl group, with a yield of 88%, an epoxy value of 0.451mol / 100g, and a refractive index of 1.63.
[0103] Infrared spectrum: 3035cm -1 、2988cm -1 (benzene ring CH bond); 2897cm -1 (alkyl CH bond); 1585cm -1 、1503cm -1 (benzene ring C=C bond); 1189cm -1 (fatty ether bond COC); 925cm -1 (Epoxy group).
[0104] 1 H NMR (400 MHz, CDCl3): δ6.7-7.7 (12H, benzene ring); δ3.9-4.2 (4H, -CH2- connected to the epoxy group); δ3.3 (2H, -CH- within the epoxy group); δ2.7-2.8 (4H, -CH2- within the epoxy group); δ0.9-2.2 (16H, -CH2CH2CH2CH2-).
[0105] Example 3
[0106] The preparation methods of the S-type epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Example 3 are similar to those of the S-type epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Example 1, except that m-hydroxyphenethyl bromide is introduced into the preparation process of the S-type epoxy compound having a binaphthyl group of Example 1. The preparation method of the S-type epoxy compound having a binaphthyl group is as follows:
[0107] In a 100 mL three-necked flask equipped with a condenser, a magnetic stirrer and a nitrogen interface, 5.73 g of (S)-(-)-1,1'-bi-2-naphthol and 100 mL of tetrahydrofuran were added, followed by 0.31 g of KOH, 0.013 g of KI and 0.73 g of m-hydroxyphenethyl bromide. The mixture was refluxed at 85 °C for 10 h under a nitrogen atmosphere, then cooled, extracted with ethyl acetate and dried to obtain an intermediate.
[0108] The above intermediate, 37g of epichlorohydrin, and 0.287g of tetrabutylammonium bromide were heated to 105°C and reacted for 3.5h, then the heating was stopped, the temperature was lowered to 50°C, and 6.93g of 30wt% NaOH solution was added dropwise using a constant pressure dropping funnel, and the addition was completed slowly within 1.5h. After reacting for 2h, the heating was stopped. After the reaction was completed, the white solid was filtered out and washed with deionized water for 3 to 4 times until the solution was neutral, anhydrous sodium sulfate was added to dry and remove water, filtered, and then the epichlorohydrin was removed by reduced pressure distillation. The mixture was heated in an oven at 150°C for 16h to obtain an S-type epoxy compound with a binaphthyl group, with a yield of 89%, an epoxy value of 0.451mol / 100g, and a refractive index of 1.67.
[0109] Infrared spectrum: 3035cm -1 、2988cm -1 (benzene ring CH bond); 2897cm -1 (alkyl CH bond); 1593cm -1 and 1499cm -1 (benzene ring C=C bond); 1183cm -1 and 1078cm -1 (ether bond COC); 918cm -1 (Epoxy group).
[0110] 1 H NMR (400 MHz, CDCl3): δ6.7-7.7 (12H, benzene ring); δ3.7-3.9 (4H, -CH2- connected to the epoxy group); δ3.1 (2H, -CH- in the epoxy group); δ2.8-2.9 (4H, -CH2- in the epoxy group); 1.8-2.1 (8H, -CH2CH2-).
[0111] Example 4
[0112] The preparation methods of the S-type epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Example 4 are similar to those of the S-type epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Example 1, except that: no photoinitiator is introduced into the curing adhesive of Example 1, and the optical film is cured by thermal curing. The preparation methods of the curing adhesive and the optical film are as follows:
[0113] Preparation of optical adhesive: 5 g of the above-mentioned S-type epoxy compound with binaphthyl group was dissolved in 4.6 g of propylene glycol methyl ether acetate, 0.4 g of curing agent dicyandiamide and 0.04 g of leveling agent BYK381 were added, and the mixture was heated and mixed at 100° C. for 20 min, and then dispersed under magnetic stirring at 600 rpm for 0.5 h to obtain a cured adhesive.
[0114] Preparation of optical film: Place a glass sheet with a diameter of 4 inches on a Laurell spin coating device, and use a pipette to drop 4 ml of the above-mentioned curing glue on the glass sheet to prepare a coating. The spin coating speed is 2000 rpm, the rotation time is 1 min, and it is placed in a drying oven at 160°C for curing. The curing time is 30 min to prepare an optical film.
[0115] Example 5
[0116] The preparation methods of the S-type epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Example 5 are similar to those of the S-type epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Example 1, except that an oligomer of the S-type epoxy compound having a binaphthyl group is introduced into the curing adhesive of Example 1, and the mass ratio of the oligomer of the S-type epoxy compound having a binaphthyl group to the S-type epoxy compound having a binaphthyl group is 0.01. The specific preparation method of the oligomer of the S-type epoxy compound having a binaphthyl group is:
[0117] Preparation of S-type oligomers of epoxy compounds with binaphthyl groups: Add 5.73 g of (S)-1,1-binaphthol, 19 g of epichlorohydrin and 0.287 g of tetrabutylammonium bromide to a 100 mL three-necked flask equipped with a condenser, a magnetic stirrer and a nitrogen interface, raise the temperature to 105°C, react for 3.5 hours, then stop heating, cool to 50°C, and use a constant pressure dropping funnel to add 3.15 g of 50% NaOH solution, slowly add it within 1.5 hours, react for 2 hours, and then stop heating. After the reaction is completed, the white solid is filtered out and washed with deionized water for 3 to 4 times until the solution is neutral. Anhydrous sodium sulfate is added to dry and remove water, filtered, and then epichlorohydrin is distilled off under reduced pressure. The mixture is heated in an oven at 150°C for 16 hours to obtain an S-type oligomer of an epoxy compound having a binaphthyl group, the refractive index of which is 1.68, and the number average molecular weight of the S-type oligomer of an epoxy compound having a binaphthyl group is 581.59 g / mol.
[0118] Embodiment 6-7
[0119] The preparation methods of the S-type epoxy compound with binaphthyl group, curing adhesive, and optical film of Examples 6 to 7 are similar to those of the S-type epoxy compound with binaphthyl group, curing adhesive, and optical film of Example 5, except that the mass ratio of the oligomer of the S-type epoxy compound with binaphthyl group to the S-type epoxy compound with binaphthyl group in Example 5 is adjusted to 0.05 and 0.055, respectively, as shown in Table 1-1 for details.
[0120] Embodiments 8 to 11
[0121] The preparation methods of the S-type epoxy compounds with binaphthyl groups, curing adhesives, and optical films of Examples 8 to 11 are similar to those of the S-type epoxy compounds with binaphthyl groups, curing adhesives, and optical films of Example 1, except that epoxy acrylate resin CN104NS, acrylate resin CN821, polyurethane acrylate CN964, and polyester acrylate CN2270NS are introduced into the curing adhesive of Example 1, and the mass ratio of the epoxy compounds with binaphthyl groups is 1:5, as shown in Table 1-1. (The above resins are all purchased from Sartomer)
[0122] Example 12
[0123] The preparation methods of the S-type epoxy compound with binaphthyl groups, the curing adhesive, and the optical film of Example 12 are similar to those of the S-type epoxy compound with binaphthyl groups, the curing adhesive, and the optical film of Example 1, except that nano-silica particles are introduced into the curing adhesive of Example 1, and the mass ratio of the nano-silica particles to the S-type epoxy compound with binaphthyl groups is 1:5, as shown in Table 1-2 for details.
[0124] Example 13
[0125] The preparation methods of the S-type epoxy compound with binaphthyl groups, the curing adhesive, and the optical film of Example 13 are similar to those of the S-type epoxy compound with binaphthyl groups, the curing adhesive, and the optical film of Example 1, except that nano-titanium dioxide particles are introduced into the curing adhesive of Example 1, and the mass ratio of the nano-titanium dioxide particles to the S-type epoxy compound with binaphthyl groups is 1:1, as shown in Table 1-2 for details.
[0126] Embodiment 14
[0127] The preparation methods of the S-type epoxy compound with a naphthyl group, the curing adhesive, and the optical film of Example 14 are similar to those of the S-type epoxy compound with a naphthyl group, the curing adhesive, and the optical film of Example 1, except that: the active monomer 3-phenoxybenzyl acrylate is introduced into the curing adhesive of Example 1, and the mass ratio of 3-phenoxybenzyl acrylate to the S-type epoxy compound with a naphthyl group is 1:5, as shown in Table 1-2 for details.
[0128] Embodiments 15 to 18
[0129] The preparation methods of the S-type epoxy compounds with binaphthyl groups, curing adhesives, and optical films of Examples 15 to 18 are similar to those of the S-type epoxy compounds with binaphthyl groups, curing adhesives, and optical films of Example 1, with the difference being that the mass content of the S-type epoxy compounds with binaphthyl groups in the curing adhesive of Example 1 is adjusted to 10%, 30%, 70%, and 90%, respectively, by adjusting the solvent content, as shown in Table 1-2.
[0130] Embodiment 19-20
[0131] The preparation methods of the S-type epoxy compound with a naphthyl group, the curing adhesive, and the optical film of Examples 19 to 20 are similar to those of the S-type epoxy compound with a naphthyl group, the curing adhesive, and the optical film of Example 2, except that the mass content of the S-type epoxy compound with a naphthyl group in the curing adhesive of Example 2 is adjusted to 20% and 80%, respectively, by adjusting the solvent content, as shown in Table 1-2.
[0132] Embodiment 21-22
[0133] The preparation methods of the S-type epoxy compound with a naphthyl group, the cured adhesive, and the optical film of Examples 21 to 22 are similar to those of the S-type epoxy compound with a naphthyl group, the cured adhesive, and the optical film of Example 3, with the difference being that the mass content of the S-type epoxy compound with a naphthyl group in the cured adhesive of Example 3 is adjusted to 20% and 80%, respectively, by adjusting the solvent content, as shown in Table 1-2.
[0134] Embodiment 23
[0135] The preparation methods of the S-type epoxy compound with binaphthyl groups, the curing adhesive, and the optical film of Example 23 are similar to those of the S-type epoxy compound with binaphthyl groups, the curing adhesive, and the optical film of Example 3, except that: an oligomer of the S-type epoxy compound with binaphthyl groups is introduced into the curing adhesive of Example 3, and the mass ratio of the oligomer of the S-type epoxy compound with binaphthyl groups to the S-type epoxy compound with binaphthyl groups is 0.05. The specific preparation method of the oligomer of the S-type epoxy compound with binaphthyl groups is shown in Example 5, and specifically in Table 1-2.
[0136] Comparative Example 1
[0137] The preparation methods of the epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Comparative Example 1 are similar to those of the S-type epoxy compound having a binaphthyl group, the curing adhesive, and the optical film of Example 1, except that the S-type epoxy compound having a binaphthyl group in Example 1 is adjusted to an R-type epoxy compound having a binaphthyl group. The specific preparation method of the R-type epoxy compound having a binaphthyl group is as follows:
[0138] In a 100 mL three-necked flask equipped with a condenser, a magnetic stirrer and a nitrogen interface, 5.73 g (R)-1,1'-bi-2-naphthol, 37 g epichlorohydrin and 0.287 g tetrabutylammonium bromide were added, the temperature was raised to 105°C, the reaction was continued for 3.5 hours, and then the heating was stopped, the temperature was lowered to 50°C, and 6.93 g 30% NaOH solution was added dropwise using a constant pressure dropping funnel, and the addition was completed slowly within 1.5 hours. After the reaction was completed, the heating was stopped. After the reaction was completed, the white solid was filtered out, and the solution was washed with deionized water for 3 to 4 times until it was neutral, anhydrous sodium sulfate was added to dry and remove water, and then the epichlorohydrin was removed by vacuum distillation. The mixture was heated in an oven at 150°C for 16 hours to obtain an R-type epoxide compound with a bi-naphthyl group, with a yield of 91%, an epoxy value of 0.466 mol / 100 g, and a refractive index of 1.64.
[0139] Infrared spectrum: 3052cm -1 、2937cm -1 (benzene ring CH bond); 2887cm -1 (alkyl CH bond); 1600cm -1 、1499cm -1 (Benzene ring C=C bond); 920cm -1 (Epoxy group).
[0140] 1 H NMR (400 MHz, CDCl3): δ 6.8-7.9 (12H, benzene ring); δ 3.9-4.2 (4H, -CH2- connected to the epoxy group); δ 3.3 (2H, -CH- in the epoxy group); δ 2.7-2.8 (4H, -CH2- in the epoxy group).
[0141] Comparative Example 2
[0142] The preparation methods of the epoxy compound with binaphthyl groups, cured adhesive, and optical film of Comparative Example 2 are similar to those of the S-type epoxy compound with binaphthyl groups, cured adhesive, and optical film of Example 1, except that the S-type epoxy compound with binaphthyl groups in the cured adhesive of Example 1 is adjusted to a mixture of an R-type epoxy compound with binaphthyl groups and an S-type epoxy compound with binaphthyl groups in a molar ratio of 1:1. The preparation method of the R-type epoxy compound with binaphthyl groups is shown in Comparative Example 1, and specifically in Table 1-2.
[0143] Comparative Example 3
[0144] The preparation methods of the epoxy compound with binaphthyl group, curing adhesive and optical film of Comparative Example 3 are similar to those of the S-type epoxy compound with binaphthyl group, curing adhesive and optical film of Example 4, except that the S-type epoxy compound with binaphthyl group of Example 4 is adjusted to an R-type epoxy compound with binaphthyl group. The preparation method of the R-type epoxy compound with binaphthyl group is shown in Comparative Example 1, and specifically in Table 1-2.
[0145] Comparative Example 4
[0146] The preparation methods of the epoxy compound with binaphthyl group, curing adhesive and optical film of Comparative Example 4 are similar to those of the S-type epoxy compound with binaphthyl group, curing adhesive and optical film of Example 8, except that the S-type epoxy compound with binaphthyl group of Example 8 is adjusted to an R-type epoxy compound with binaphthyl group. The preparation method of the R-type epoxy compound with binaphthyl group is shown in Comparative Example 1, and specifically in Table 1-2.
[0147] Comparative Example 5
[0148] The preparation methods of the epoxy compound with binaphthyl group, curing adhesive and optical film of Comparative Example 5 are similar to those of the S-type epoxy compound with binaphthyl group, curing adhesive and optical film of Example 12, except that the S-type epoxy compound with binaphthyl group of Example 12 is adjusted to an R-type epoxy compound with binaphthyl group. The preparation method of the R-type epoxy compound with binaphthyl group is shown in Comparative Example 1, and specifically in Table 1-2.
[0149] Table 1-1 Preparation parameters of Examples 1 to 11
[0150]
[0151] Table 1-2 Preparation parameters of Examples 12 to 23 and Comparative Examples 1 to 5
[0152]
[0153] 2. Test Method
[0154] 1) Specific rotation test of S-type epoxy compounds with binaphthyl groups
[0155] The specific rotation of S-type epoxy compounds with binaphthyl groups was tested with reference to GB / T 613-2007 standard. The S-type epoxy compounds with binaphthyl groups to be tested were dissolved in DMSO to prepare a solution with a concentration of 1g / 100mL, and placed in a polarimeter for testing. The test wavelength was 589nm, the test temperature was 20℃, and the test equipment model was German KRÜSS P8000.
[0156] 2) Yellowness and APHA test of S-type epoxy compounds with binaphthyl groups
[0157] The yellowness of the S-type epoxy compound with binaphthyl group to be tested was dissolved in acetone solvent and then spin-coated on a glass substrate, then placed in an oven at 80°C for drying, and then tested using a colorimeter. The test equipment model is American X-Rite Ci7800.
[0158] 3) Test of initial decomposition temperature of S-type epoxy compounds with binaphthyl groups
[0159] The initial decomposition temperature of S-type epoxy compounds with binaphthyl groups was tested with reference to GB / T 33047.1-2016 standard. Weigh 3-7 mg of the S-type epoxy compound with binaphthyl groups to be tested, put it into an alumina crucible and record the thermal degradation behavior of the test object in a nitrogen atmosphere. The temperature range is 50-800℃, the heating rate is 10℃ / min, and the test equipment model is Mettler TGA2. Initial decomposition temperature T 5wt% It is taken from 5wt% of the temperature curve loss The temperature value corresponding to the point.
[0160] 4) Test of the number average molecular weight of oligomers of S-type epoxy compounds with binaphthyl groups
[0161] The S-type oligomer of the epoxide compound with a binaphthyl group to be tested was completely dissolved in tetrahydrofuran (THF) and diluted to a 25 mL volumetric flask. It was filtered with a polytetrafluoroethylene filter before injection. The test equipment was gel chromatography GPC, the mobile phase was chloroform, and each sample was run at a flow rate of 1 mL / min for 30 min.
[0162] 5) Test of refractive index of optical film
[0163] The refractive index of the optical film was tested according to GB / T 6488-2008 standard. The refractive index of the optical film to be tested was tested at 20°C using an ellipsometer (SemilabSE-2000).
[0164] 6) Test of optical film transmittance
[0165] The transmittance of the optical film was tested with reference to GB / T 2410-2008 standard. The transmittance of the optical film prepared on the glass substrate was tested with a UV-Vis spectrophotometer in the range of 400nm~800nm. The test equipment model was Shimadzu UV-1800.
[0166] 7) Test of yellowness value of optical film
[0167] Initial yellowness value test: The optical film prepared on the glass substrate is tested for yellowness value using a colorimeter. The test equipment model is American X-Rite Ci7800.
[0168] Yellowness value test after high-temperature storage: The optical film prepared with a glass substrate was placed in a 230°C oven for 1 hour. After being taken out, the yellowness value was tested using a colorimeter. The test equipment model was American X-Rite Ci7800.
[0169] Table 2 Performance parameters of various embodiments and comparative examples
[0170]
[0171] III. Analysis of test results of various embodiments and comparative examples
[0172] It can be seen from Examples 1 to 23 and Comparative Examples 1 to 5 that, compared with R-type epoxy compounds having binaphthyl groups or R-type / S-type epoxy compound mixtures having binaphthyl groups, the curing adhesive containing S-type epoxy compounds having binaphthyl groups not only has the advantages of high refractive index and low yellowness, but more importantly, the curing adhesive has greater advantages in the curing process, and the prepared optical film has the advantages of lower yellowness, higher light transmittance and temperature resistance, which broadens the application window of the curing adhesive.
[0173] It can be seen from Example 1 and Comparative Examples 1-2, Example 4 and Comparative Example 3, Example 8 and Comparative Example 4, and Example 12 and Comparative Example 5 that, compared with the R-type epoxy compound with a naphthyl group or the R-type / S-type epoxy compound mixture with a naphthyl group, the S-type epoxy compound with a naphthyl group not only has a lower yellowness value and APHA, but also the optical film prepared with its cured adhesive has a significantly lower yellowness value, a significantly higher light transmittance, and a further difference in yellowness value after high-temperature storage. The optical performance advantage of the cured adhesive containing the S-type epoxy compound with a naphthyl group is outstanding.
[0174] It can be seen from Examples 1 and 2 that the introduction of long-chain alkyl groups in S-type epoxy compounds having a naphthyl group is beneficial to reducing the yellowness value thereof, and further reducing the yellowness value of the optical film thereof and the yellowness value after high-temperature storage; it can be seen from Examples 1 and 2 that the introduction of phenyl groups in S-type epoxy compounds having a naphthyl group is beneficial to increasing the refractive index thereof, and further increasing the refractive index of the optical film thereof.
[0175] It can be seen from Example 1 and Example 4 that both photocuring and thermal curing can be used to prepare the cured adhesive, and the optical films prepared therefrom have the advantages of high refractive index, low yellowness, high light transmittance and high temperature resistance.
[0176] It can be seen from Examples 1 and 5 to 7, and Examples 3 and 23 that by introducing an S-type oligomer of an epoxy compound having a dinaphthyl group into the curing adhesive and controlling its content within 0.055 wt %, the refractive index of the optical film can be increased without significantly affecting its yellowness value and transmittance.
[0177] It can be seen from Examples 1 and 8 to 14 that the S-type epoxy compounds having a binaphthyl group have excellent compatibility with resins, active monomers, and nanoparticles, and can be used to prepare optical films with high refractive index, low yellowness, high light transmittance, and high temperature resistance.
[0178] It can be seen from Examples 1 and 15 to 18, Example 2 and 19 to 20, and Example 3 and 21 to 22 that, based on the total mass of the cured adhesive, the mass content of the S-type epoxy compound having a binaphthyl group is controlled at 10% to 90%, and optical films with high refractive index, low yellowness, high transmittance and high temperature resistance can be prepared.
[0179] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A curing adhesive, characterized in that: Including S-type epoxy compounds having a binaphthyl group, wherein the S-type epoxy compounds having a binaphthyl group include compounds having a structure shown in formula I, Formula I, Wherein R1 includes substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 1-10 Alkyleneoxy, substituted or unsubstituted C 3-10 At least one of a cycloalkoxy group and a substituted or unsubstituted phenoxy group.
2. The curing adhesive according to claim 1, characterized in that: The curing adhesive further comprises the oligomer of the S-type epoxy compound having binaphthyl groups, and the mass ratio of the oligomer of the S-type epoxy compound having binaphthyl groups to the S-type epoxy compound having binaphthyl groups is not higher than 0.
055.
3. The curing adhesive according to claim 1, characterized in that: R1 includes substituted or unsubstituted C 1-10 Alkyleneoxy, substituted or unsubstituted C 3-10 At least one of a cycloalkoxy group and a substituted or unsubstituted phenoxy group.
4. The curing adhesive according to claim 1, characterized in that: The curing adhesive further comprises at least one of a resin, an active monomer, an auxiliary agent, and a solvent; The resin includes at least one of epoxy acrylate resin, polyurethane acrylate resin, polyether acrylate resin, polyester acrylate resin, polyurethane, polyurethane resin, and silicone resin; The active monomer includes at least one of epoxy monomers, acrylate monomers, and styrene monomers. The epoxy monomer includes at least one of ethylene oxide, propylene oxide, butylene oxide, alkyl ethylene oxide with alkyl carbon atoms of 3 to 20, styrene oxide, 1,3-butadiene diepoxide, 1,5-hexadiene diepoxide, 1,7-octadiene diepoxide, 1,4-butanediol diglycidyl ether, neopentyl glycol diglycidyl ether, styrene oxide, alkyl glycidyl ether, aromatic glycidyl ether, alkenyl glycidyl ether, alkynyl glycidyl ether, and cyclohexene oxide. The acrylate monomer includes at least one of tricyclodecane dimethanol diacrylate, tricyclodecane dimethanol Dimethyl diacrylate, neopentyl glycol diacrylate, dipropylene glycol diacrylate, diethylene glycol diacrylate, diethylene glycol dimethacrylate, triethylene glycol diacrylate, ethylene glycol diacrylate, 1,3-butylene glycol dimethacrylate, 1,4-butylene glycol diacrylate, 1,4-butylene glycol di(meth)acrylate, neopentyl glycol dimethacrylate, propoxylated neopentyl glycol diacrylate, tripropylene glycol diacrylate, 1,6-hexanediol diacrylate, 1,6-hexanediol dimethacrylate, dipropylene glycol diacrylate, ethoxylated bisphenol A dimethacrylate, tripropylene glycol diacrylate, pentaerythritol dimethacrylate , trimethylolpropane triacrylate, pentaerythritol triacrylate, dipentaerythritol hexaacrylate, urethane di(meth)acrylate, bisphenol A propylene glycol dimethacrylate, trimethylolpropane tri(meth)acrylate, ethoxylated trimethylolpropane triacrylate, pentaerythritol tetraacrylate, isobornyl methacrylate, isobornyl acrylate, isooctyl acrylate, isooctyl methacrylate, tetrahydrofuran acrylate, tetrahydrofuran methacrylate, 2-phenoxyethyl acrylate, pentaerythritol (meth)acrylate, n-butyl acrylate, isodecyl acrylate, lauric acid acrylate, cyclohexyl acrylate, 3,3,5-trimethylcyclohexyl acrylate, 4- At least one of tert-butylcyclohexyl acrylate, dicyclopentenyl acrylate, octadecyl methacrylate, butyl acrylate, isodecyl acrylate, isodecyl methacrylate, lauryl acrylate, lauryl methacrylate, glycidyl methacrylate, 2-phenoxyethyl methacrylate, isodecyl acrylate, vinyl acetate, dicyclopentenyl ethoxylated methacrylate, and 4-tert-butylcyclohexyl acrylate, and the styrene monomer includes at least one of styrene, vinyltoluene, α-methylstyrene, p-methylstyrene, α-butylstyrene, 4-n-butylstyrene, divinylbenzene, 2,4-dimethylstyrene, ethylstyrene, and p-tert-butylstyrene; The auxiliary agent includes at least one of a photoinitiator, a leveling agent, and an antioxidant; The solvent includes at least one of propylene glycol methyl ether acetate, propylene glycol methyl ether, methyl ethyl ketone, methyl isobutyl ketone, butyl acetate, and ethanol.
5. The curing adhesive according to claim 4, characterized in that: Based on the total mass of the curing glue, the mass content of the S-type epoxy compound having a binaphthyl group is 10% to 90%, the mass content of the solvent is 5% to 88%, the mass content of the auxiliary agent is 0.1% to 5%, the mass content of the resin is 0% to 30%, and the content of the active monomer is 0% to 30%.
6. The curing adhesive according to any one of claims 1 to 5, characterized in that: The curing glue further includes nanoparticles, and the nanoparticles include at least one of SiO2, ZnS, ZnO, CeO2, GeO2, Ta2O5, Bi4Ti3O2, Nb2O5, ITO, HfO2, SnO2, MoO3, Sb2O3, Sb2O5, Nd2O3, ZrO2, and TiO2; Calculated based on the total mass of the cured adhesive, the mass content of the nanoparticles is 0% to 60%.
7. A method for preparing the S-type epoxy compound having a binaphthyl group according to any one of claims 1 to 6, comprising: Under reactive conditions, reacting raw materials including (S)-(-)-1,1'-binaphthol and epoxy halogenated alkyl to prepare the S-type epoxy compound having a binaphthyl group; Wherein, the epoxyhaloalkane comprises at least one of the compound of the structure shown in Formula II and the compound of the structure shown in Formula III, Formula II, Formula III, In the formula, R 11 , R 12 Each independently includes substituted or unsubstituted C 1-10 At least one of the alkylene groups, Y1 and Y2 each independently include at least one of bromine, fluorine, chlorine and iodine.
8. The preparation method according to claim 7, characterized in that: The raw materials also include compounds with the structure shown in formula IV, Formula IV, In the formula, R 13 Including substituted or unsubstituted C 1-10 Alkylene, substituted or unsubstituted C 3-10 At least one of cycloalkyl, substituted or unsubstituted phenyl, X1 comprises at least one of bromine, fluorine, chlorine, and iodine; The epoxyhaloalkane includes at least one of epichlorohydrin, 1,2-epoxychlorobutane, 2-(4-chlorobutyl)ethylene oxide, (8-chlorooctyl)ethylene oxide, epibromohydrin, epiiodohydrin, 2-(bromomethyl)-2-methylethylene oxide, and 3-chloro-2-methyl-1,2-epoxypropane.
9. An S-type epoxy compound having a binaphthyl group, characterized in that: Prepared by the preparation method described in claim 7 or 8.
10. Use of the curing adhesive according to any one of claims 1 to 6 in optical devices.
Citation Information
Patent Citations
Epoxy resin having binaphthalene skeleton
CN105579488A
Binaphthol-based epoxy resin monomer, preparation method thereof and application of binaphthol-based epoxy resin monomer in preparation of full-bio-based epoxy resin
CN115197174A
Chiral quaternary ammonium salt with (S)-binaphthyl as well as preparation method and application of chiral quaternary ammonium salt
CN115260126A
Curable composition, cured product, optical member, and optical device
CN117467239A
Preparation method of chiral binaphthyl functional group epoxy resin
CN118459725A